The role(s) of community health workers in primary health care reform in Kerala, before and during the COVID 19 pandemic: a qualitative study - Sankar D, Hari; Joseph, Jaison; Benny, Gloria; Surendran, Surya; Sharma, Santosh Kumar; Nambiar, Devaki (Frontiers in Health Services, 2024)
Background Accredited Social Health Activists (ASHA) are Community Health Workers (CHWs) employed by the National Health Mission of the Government of India to link the population to health facilities and improve maternal and child health outcomes in the country. The government of Kerala launched primary health reform measures in 2016 whereby Primary Health Centres (PHCs) were upgraded to Family Health Centres (FHCs). The COVID-19 pandemic in 2020 impacted essential health service delivery, including primary care services. The CHWs network of Kerala played a crucial role in implementing the primary care reforms and COVID-19 management efforts that followed. We carried out a study to understand the perspectives of the CHWs in Kerala about their role in the recent primary healthcare reforms and during the COVID-19 pandemic management efforts. Methods We conducted in-depth interviews (IDI) with 16 ASHAs from 8 primary care facilities in Kerala from July to October 2021. We further conducted Focus Group Discussions (FGDs) (N = 34) with population subgroups in these eight facility catchment areas and asked their opinion about the ASHAs working in their community. We obtained written informed consent from all the participants, and interview transcripts were thematically analysed by a team of four researchers using ATLAS.ti 9 software. Results Our study participants were women aged about 45 years with over 10 years of work experience as CHWs. Their job responsibilities as a frontline health worker helped them build trust in the community and local self-governments. CHWs were assigned roles of outpatient crowd management, and registration duties in FHCs. The COVID-19 pandemic increased their job roles manifold. Community members positively mentioned the home visits, delivery of medicines, and emotional support offered by the CHWs during the pandemic. The CHWs noted that the honorarium of INR 6,000 (US73) was inconsistent and very low for the volume of work done. Conclusion The CHWs in Kerala play a crucial role in primary care reforms and COVID-19 management. Despite their strong work ethic and close relationship with local self-governments, low and irregular wages remain the biggest challenge.